Viability of Probiotic Bacteria During Refrigerated Storage in Commercial Yogurt Marketed in Mashhad, Iran - Sayyadi, Masoume; Sani, Ali Mohamadi (Asian Journal of Biological and Life Sciences, 2017)
Probiotic yogurt is one of the most common and important probiotic products in the market. Researchers have revealed that the survival of probiotic organisms in yogurt during storage has often been low. This research aimed to investigate the viability of probiotic bacteria in yogurt (Lactobacillus acidophilus and Bifidobacterium bifidum ) marketed in Mashhad during storage at refrigerator. Methods based on culture using two culture media (MRS/CL/CIP for L.acidophilus and TOS-MUP for B.bifidum) was used. Results showed in 40% of samples the number of viable lactobacillus acidophilus was lower than the standard limit (6 log cfu/ml) and about B.bifidum only 13% of samples had viable bacteria lower than the limit. Comparison between the number of two type of viable bacteria showed the average of viable L.acidophilus and B.bifidum in all samples of yogurt was 6.37 log CFU / ml and 6.06 log CFU/ml, respectively. These amounts were significantly different (p<0.05). It is concluded that the counts of probiotic bacteria in half of the tested yogurt was higher than the international standard limit.
Keywords: Bifidobacterium bifidum; Lactobacillus acidophilus; Probiotic yogurt